2001
DOI: 10.1046/j.1440-1614.2001.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

From source material to news story in New Zealand print media: a prospective study of the stigmatizing processes in depicting mental illness

Abstract: Although there were no inaccuracies in the content of the news stories they were substantially more negative than the source material in their depiction of the identified patient. A potentially positive discourse (human rights) was not by itself sufficient to ensure a positive portrayal of mental illness. An understanding of the transformations is important for efforts to effectively combat the stigmatization of those with mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
0
21
0
2
Order By: Relevance
“…Psychosis seems to be the most stigmatized mental disorder, a result also found in several similar studies (e.g., Boke et al, 2007; Francis et. al., 2004; Nairn et al, 2001; Stuart, 2003). Building upon the results of recent study among German citizens, even improving mental health literacy about mental illnesses and in particular about schizophrenia does not necessarily lead to improvement of public attitudes toward people with mental illness (Angermeyer, Holzinger, & Matschinger, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Psychosis seems to be the most stigmatized mental disorder, a result also found in several similar studies (e.g., Boke et al, 2007; Francis et. al., 2004; Nairn et al, 2001; Stuart, 2003). Building upon the results of recent study among German citizens, even improving mental health literacy about mental illnesses and in particular about schizophrenia does not necessarily lead to improvement of public attitudes toward people with mental illness (Angermeyer, Holzinger, & Matschinger, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our work leads to the conclusion that, even though the media rarely offer misinformation about mental disorders, as Nairn et al (2001) found in New Zealand, the emergence of stereotypes and negative treatment information generally perpetuate the transmission of social stigma. Specifically, 25% of the information analyzed in this work was stigmatizing.…”
Section: Discussionmentioning
confidence: 73%
“…La representación de la enfermedad mental en la prensa es predominantemente negativa (e.g, Coverdale et al, 2002;Nairn, Coverdale y Claasen, 2001;Walh et al, 2002), apareciendo ligada con frecuencia a sucesos violentos y delictivos (e.g., Angermeyer y Schulze, 2001;Coverdale et al, 2002;Gamo, 1992;Huang y Pruebe, 2003;Instituto Andaluz de Salud Mental, 1987). Generalmente se destacan los aspectos negativos, con una escasa presencia de informaciones sobre personas con trastorno mental que llevan una vida normalizada.…”
Section: Introductionunclassified
See 2 more Smart Citations